A bibliometric analysis of Burnout Syndrome and its impact on managerial performance in international research - Almeida, Ricardo Santana de; Almeida, Debora Pinheiro Santana de; Strassburg, Udo; Martins, Vinicius Abílio (Brazilian Journal of Production Engineering, 2026)
When conducting research, understanding the state of the art is essential, as it enables the identification of the evolution of a given topic and supports the selection of relevant scientific literature. Accordingly, this study aims to analyze the state of the art of research that investigates the impact of burnout syndrome on managerial performance. Bibliometrics was adopted as the methodological approach, as it is based on mathematical and statistical techniques applied to the analysis of scientific publications. This study is characterized as descriptive, bibliographic, and quantitative. Data collection was carried out using the Knowledge Development Process – Constructivist (ProKnow-C), resulting in a bibliographic portfolio consisting of 45 international scientific articles. Data analysis was based on Bradford’s Law, to assess journal relevance, and Zipf’s Law, to examine keyword frequency. The results reveal a significant increase in publications over the last two years, accounting for 27% of the total analyzed studies, as well as a concentration of publications in journals such as the Journal of Organizational Behavior and the Journal of Applied Psychology. The findings indicate a growing academic interest in the relationship between burnout syndrome and managerial performance in the organizational context.
Keywords: Bibliometric; Bournout; Performance; Bradford Law; Zipf Law